Acute meningitis of piglets and mice caused by co-infected with Streptococcus suis and Aerococcus viridans. (May 2017) - Pan, Zihao; Ma, Ye; Ma, Jiale; Dong, Wenyang; Yao, Huochun
Abstract: The two opportunistic pathogens, Streptococcus suis ( S. suis ) and Aerococcus. viridans ( A. viridans ) were isolated from the brains of piglets suffered bacterial meningitis in a farm of China. The murine model has been established to evaluate the pathogenicity and symbiotic relationship of S. suis and A. viridans simultaneously infection. Our results demonstrated the ability of new serotype S. suis to cause the classical bacterial meningitis and death were greatly enhanced during co-infection with A. viridans in mice at a proportion. We also examined the distribution and titer of bacteria coinfection in organs, the titer of S. suis appeared a significant trend for an increase in the lung meanwhile the concentration titer of A. viridans maintain a low level. This is the first reported the A. viridans and S. suis coinfection cause the bacterial meningitis outbroke in the piglets and mice. Moreover, further investigation of the pathogenesis of A. viridans and S. suis is urgently needed in swine industry. Highlights: This is the first reported the A. viridans and S. suis coinfection cause the bacterial meningitis outbroke in the piglets and mice. We have developed the murine meningitis for evaluating the pathogenicity and symbiotic relationship of S. suis and A. viridans simultaneously infection. We demonstrated that a prescribed proportion of the sum for two pathogens due to the minimum LD50 in mice.